Efektivitas Program Pos Kesehatan Desa (Poskesdes) di Kampung Warungceuri Desa Nyangkowek Kecamatan Cicurug Kabupaten Sukabumi - Hasya Yushini; Julianes Cadith; Arenawati (Epistemik Press, 2022)
The focus of this research is the effectiveness of the Village Health Post Program (POSKESDES) in Warungceuri Village, Nyangkowek Village, Cicurug District, Sukabumi Regency. The purpose of this study was to determine the effectiveness of the Village Health Post Program (POSKESDES) in Warungceuri Village, Nyangkowek Village, Cicurug District, Sukabumi Regency. The theory used is the theory of effectiveness according to Sutrisno and Budiani with indicators of effectiveness, namely understanding the program, being on target, being on time for the amount of program achieved, the real change being, program socialization, and the program. The method used is descriptive quantitative. The population of this study is the community of Nyangkowek Village who are users of the POSKESDES program with a total sample of 184 people. The sampling technique used is proportional stratified random sampling technique. Data analysis was carried out through statistical testing of SPSS version 24. The results obtained in this study were 75% and included in the effective category. Suggestions in this study are to further improve the socialization program, supervise program implementation, implement new cadres and involve the community directly and carry out skills training in implementing programs for old cadres and prospective cadres.